(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Boiko, M.F. Lobachevska O.V., Kyiak N.Y., Baik O.L., Khorkavtsiv Y.D., Sohanchak R.R., Karpinets L.I., Boiko I.V., Beshley S.V., Rabyk I.V., Scherbachenko O.I., Kit N.A. Stability and adaptive structural and functional changes of mosses under the influence of abiotic stressors in an anthropogenically transformed environment. Lviv, HALICH-PRESS, 2022, 280 р. ISBN 978-617-7617-93-7